Case Series: Video-Assisted Minimally Invasive Cardiac Surgery During Pregnancy - Lu, Anyi; Ye, Yingxian; Hu, Jiaqi; Wei, Ning; Wei, Jinfeng; Lin, Bimei; Wang, Sheng (Frontiers in Medicine, 2021)
Surgical intervention is expected to improve maternal outcomes in pregnant patients with heart disease once the conservative treatment fails. For pregnant patients with heart disease, the risk of cardiac surgery under CPB must be balanced due to the high fetal loss. The video-assisted minimally invasive cardiac surgery (MICS) has been progressively applied and shows advantages in non-pregnant patients over the years. We present five cases of pregnant women who underwent a video-assisted minimally invasive surgical approach for cardiac surgery and the management strategies. In conclusion, the video-assisted minimally invasive approach for cardiac surgery is feasible and safe to pregnant patients, with good maternal and fetal outcomes under the multidisciplinary assessment and management.